2022
DOI: 10.3389/fcell.2022.949690
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in osteoarthritis: Updated insights on pathogenesis, diagnosis, and treatment

Abstract: Osteoarthritis (OA) has remained a prevalent public health problem worldwide over the past decades. OA is a global challenge because its specific pathogenesis is unclear, and no effective disease-modifying drugs are currently available. Exosomes are small and single-membrane vesicles secreted via the formation of endocytic vesicles and multivesicular bodies (MVBs), which are eventually released when MVBs fuse with the plasma membrane. Exosomes contain various integral surface proteins derived from cells, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 127 publications
(147 reference statements)
0
19
0
Order By: Relevance
“…Exosomal miRNAs (such as miR-100–5p, miR-135b, miR-92a-3p, miR-140–5, miR-23b, miR-125b, miR-126–3p, miR-320) and lncRNAs like KLF3-AS1 and their interactions with diverse signaling pathways are primarily responsible for the therapeutic potential of MSCs-sEVs in the treatment of articular cartilage and OA. , The function of miRNAs in sEVs derived from synovial fluid, focusing on their impact on chondrocyte inflammation, proliferation, and survival, as well as their potential effect on cartilage degeneration in an OA model in rats was examined. Nineteen miRNAs were identified whose expression levels differed between OA patients and healthy controls.…”
Section: Applications Of Evs-loaded Hydrogels In Tissue Regenerationmentioning
confidence: 99%
“…Exosomal miRNAs (such as miR-100–5p, miR-135b, miR-92a-3p, miR-140–5, miR-23b, miR-125b, miR-126–3p, miR-320) and lncRNAs like KLF3-AS1 and their interactions with diverse signaling pathways are primarily responsible for the therapeutic potential of MSCs-sEVs in the treatment of articular cartilage and OA. , The function of miRNAs in sEVs derived from synovial fluid, focusing on their impact on chondrocyte inflammation, proliferation, and survival, as well as their potential effect on cartilage degeneration in an OA model in rats was examined. Nineteen miRNAs were identified whose expression levels differed between OA patients and healthy controls.…”
Section: Applications Of Evs-loaded Hydrogels In Tissue Regenerationmentioning
confidence: 99%
“…Exosomes, as key vehicles for intercellular signal transmission, provide a more advantageous way to evaluate the pathological cells or tissue morphology in osteoarthritis [ 107 ]. In addition to promoting angiogenesis, bone remodeling, and chondrocyte proliferation and migration, exosomes can inhibit osteoarthritic chondrocyte apoptosis and reduce cartilage inflammation [ 107 ].…”
Section: Role Of Exosomes As Drug Delivery Systems In Bone-related Di...mentioning
confidence: 99%
“…Exosomes, as key vehicles for intercellular signal transmission, provide a more advantageous way to evaluate the pathological cells or tissue morphology in osteoarthritis [ 107 ]. In addition to promoting angiogenesis, bone remodeling, and chondrocyte proliferation and migration, exosomes can inhibit osteoarthritic chondrocyte apoptosis and reduce cartilage inflammation [ 107 ]. Therefore, exosomes derived from BMSCs, adipose mesenchymal stem cells (AMSCs), synovial mesenchymal stem cells (SMSCs), human embryonic stem cells (HESCs), and other types of MSCs can be used as DDS to treat osteoarthritis [ 108 ] ( Figure 5 ).…”
Section: Role Of Exosomes As Drug Delivery Systems In Bone-related Di...mentioning
confidence: 99%
“…58,59 However, most studies have focused on the RNA and protein content of EVs, while little has been reported on the DNA carried within them. [60][61][62][63] Takahashi et al showed that EVs maintain cellular homeostasis and prevent aberrant activation of the innate immune response by expelling damaged DNA from cells, and when this process is impaired, the DNA they carry can activate inflammatory factors including the cGAS-STING pathway and the AIM2 inflammasome. 64 In the study of the gastrointestinal response to the chemotherapeutic agent irinotecan, Lian et al found that chemotherapy-induced the release of large amounts of double-stranded DNA from exosomes in the gastrointestinal tract, and this "auto-DNA" entered the cytoplasm of innate immune cells and activated AIM2 inflammasome.…”
Section: Extracellular Vesicles -Aim2mentioning
confidence: 99%